2007
DOI: 10.1021/bi7004416
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Flexibility of the Bacterial Reaction Center:  The Wild-Type Protein Is More Rigid Than Two Site-Specific Mutants

Abstract: Experimental and theoretical studies have stressed the importance of flexibility for protein function. However, more local studies of protein dynamics, using temperature factors from crystallographic data or elastic models of protein mechanics, suggest that active sites are among the most rigid parts of proteins. We have used quasielastic neutron scattering to study the native reaction center protein from the purple bacterium Rhodobacter sphaeroides, over a temperature range of 4-260 K, in parallel with two no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
60
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 67 publications
13
60
0
Order By: Relevance
“…As a complicating factor for such studies, a significant solvent contribution to the overall scattering intensity can be expected as observed before for the antenna complex LHC II [15] and for the bacterial reaction center [16,17]. In the present study we address this problem by QENS experiments on WSCP and on the corresponding buffer solution at room temperature.…”
Section: Introductionmentioning
confidence: 83%
“…As a complicating factor for such studies, a significant solvent contribution to the overall scattering intensity can be expected as observed before for the antenna complex LHC II [15] and for the bacterial reaction center [16,17]. In the present study we address this problem by QENS experiments on WSCP and on the corresponding buffer solution at room temperature.…”
Section: Introductionmentioning
confidence: 83%
“…Qualitatively, the observed temperature dependence of molecular dynamics of PS II is similar to that of other biomolecular systems [17,18,21,22], while specific transition temperatures and motional amplitudes differ. Later, QENS studies were reported for the bacterial RC of Rhodobacter sphaeroides and of two of its site-specific mutants [16]. The data reveal a dynamical transition at about 230 K, i.e.…”
Section: Qens Studies Of Ps II Membranesmentioning
confidence: 99%
“…So far, ENS and QENS have been used to study the temperature and hydration dependence of molecular dynamics in PS II membranes of green plants [10][11][12][13][14] as well as that of bacterial RCs [15,16]. This review provides a short overview about the results of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The growing conditions and the BRC purification have previously been described [9]. We used 900 nmol, 800 nmol and 1400 nmol in the WT, AA and AATyr BRCs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…sphaeroides (see Fig. 1) [8,9]. The double mutant, called later in this paper AA, has two point mutations near the Q B acidic cluster: (L212Glu/L213Asp -> Ala/Ala).…”
Section: Introductionmentioning
confidence: 99%